The construction of science and technology culture on the development of Suramadu bridge - Jatnika, Asep Wawan; Sinaga, Anggiat; Munaf, Dicky R. (2006)
The Construction of Suramadu Bridge is a technological product in view of people knowledge, which means that besides construction technology, its include the society development process. Learning from the previous bridge construction around the world, its also important to consider the human resources and societal adaptability to accept the bridge. The sociotechnology approach in this paper, gives a new perspective for develop Science and Technology Culture.